Author Correction: Carotid imaging changes and serum IL-1β, sICAM-1, and sVAP-1 levels in benign paroxysmal positional vertigo - Xiaoxu Chen; Huimin Feng; Hongjin Liu; Xianrong Xu; Jianchang Wang; Zhanguo Jin (Scientific Reports, 2021)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.